The Impact of Social Media on Navodit College Students - Adhikari, Anup (Nepal Journal of Multidisciplinary Research, 2020)
Today social media has been commonly used by everyone especially the young people and the institutions too are getting in to this modern medium of communication rapidly. It has created a new world of collaborations and communication. And it has also facilitated an easy and economical way of communication between friends and families across the world. On the other side, social media has dragged the youngsters and students into it and to the extent that it fritters away their valuable time, energy and money. Many students spent most of the time in those sites which ultimately does not contribute to their lives as well as in their academic life.Now-a-days, many social media have been invented from local and multinational company in national and international level. The purpose of this research paper is to assess the impact of social media on Navodit College students. The researcher tries to examine and identify the impact of social media in the research. The objective of this study was to explore and investigate the factors compelling the college students to using social media. Qualitative and Quantitative, both research methods were used while conducting the research and this research is done in Navodit College (Tribhuvan University, Nepal). 109 Bachelors level students was involved to fill up the questionnaire of the academic year of 2019/2020. Research upon social media is more important because it has both positive and negative impact upon the students in their psychological and physical aspect.